Efficacy of Bone Marrow Aspirates in Bone Regeneration Compared to Conventional Bone Grafts- A Systematic Review - Kadic, Hannah (2026)
The search for a superior bone graft substitute compared to the gold standard of harvesting autogenous bone grafts has plagued dentists for decades. With the advent of tissue engineering, the search has been aimed at bone graft substitutes with osteogenic potential and osteoinductive and osteoconductive properties. Bone Marrow Aspirates (BMAs) have evolved as a potential adjunct to conventional bone grafts that can substantially enhance the bone regeneration potential of these materials. This systematic review aims to explore and assess the literature on the efficacy of bone marrow aspirates in new bone formation. An electronic search of PubMed, Web of Science, and Scopus databases was conducted to identify articles that evaluated the efficacy of bone marrow aspirates for new bone formation, published until September 2022, and a supplementary manual search of references from these articles was also conducted. Case reports, case series, commentaries, letters to the editor, narrative or systematic reviews, and articles in languages other than English were excluded from consideration. The articles were assessed against the ROB-II tool for Randomised Controlled Trials (RCTs) for risk of bias assessment. GRADE assessment based on the Cochrane Handbook for quality assessment and a summary of findings table were used to present the results. In a comprehensive electronic search of 150 articles from the three databases, seven studies assessed new bone formation in healthy partially edentulous patients who underwent bone regeneration with bone marrow aspirates compared to conventional bone grafts - autogenous harvested bone, allogenic, and alloplastic substitutes. This review concludes that adding bone marrow aspirates results in comparable results to bone graft alone. The results must be interpreted cautiously owing to their 'low quality' GRADE assessment. Future research with a greater sample size, homogenous populations, and comparable digital imaging and software may provide results that can be aptly applied to broader populations.